Miscellaneous Sumerian Texts, I - Sjöberg, Åke W.
ersch. 1977; copies N 3701 and 6 N-T 636 by Darlene Loding, photos UM 29-15-132, 29-15-254 (A), 29-13-594 (B), 3 N-T 500, UM 29-15-979; hymns to Hammurabi, Nippur, Ninurta with prayer for Išmedagan.